2002
DOI: 10.1111/1471-6402.t01-1-00068
|View full text |Cite
|
Sign up to set email alerts
|

Ambivalent Sexism and Attitudes Toward Wife Abuse in Turkey and Brazil

Abstract: Men and women in Turkey and Brazil completed the Ambivalent Sexism Inventory (Glick & Fiske, 1996) and measures of attitudes about wife abuse. In both nations hostile sexism (HS) and benevolent sexism (BS) positively correlated with attitudes that legitimize abuse. Regression analyses revealed that HS accounted for unique variance, but BS (once HS was controlled) was unrelated to wife abuse attitudes. These results: (a) add to the evidence for the cross-cultural validity of ambivalent sexism, (b) suggest that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
194
2
22

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 227 publications
(246 citation statements)
references
References 12 publications
28
194
2
22
Order By: Relevance
“…Our results also revealed that respondents with higher levels of acceptability presented higher scores of ambivalent sexism, in particular in the hostile sexism subscale. Sexism has also been previously related to attitudes justifying IPVAW (e.g., Glick et al, 2002;Herrera, Expósito & Moya, 2012;Herrero et al, 2017;Valor-Segura, Expósito, & Moya, 2011).…”
Section: Discussionmentioning
confidence: 96%
“…Our results also revealed that respondents with higher levels of acceptability presented higher scores of ambivalent sexism, in particular in the hostile sexism subscale. Sexism has also been previously related to attitudes justifying IPVAW (e.g., Glick et al, 2002;Herrera, Expósito & Moya, 2012;Herrero et al, 2017;Valor-Segura, Expósito, & Moya, 2011).…”
Section: Discussionmentioning
confidence: 96%
“…Research on ambivalent sexism has shown that those who are high in hostile sexism are more tolerant of intimate partner violence (Glick, Sakalli-Ugurlu, Ferreira, & Souza, 2002) while benevolent sexism have been related to victim-blaming attitudes (Viki & Abrams, 2002) toward women. These attitudes serve as an anchorage that guides the information interpretation, supporting preconceptions against women (Fariña, Arce, & Novo, 2002), which contributes to sustain offending (Maruna, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding sexist beliefs, hostile sexism (legitimisation of violence against women challenging the power of men) supports the justification of IPV, victim blaming and exonerating perpetrators (Glick, Sakalli-Ugurlu, Ferreira, & de Souza, 2002;Sakalli, 2001). So-called benevolent sexism also considers IPV legitimate when women do not fulfil their traditional roles (Glick et al, 2002;Valor-Segura et al, 2008;Valor-Segura et al, 2011).…”
Section: Attitudes To and Beliefs About Ipvmentioning
confidence: 99%